INTERNAL CONTROL PART OF FRAUD PREVENTION IN ACCOUNTING INFORMATION SYSTEM - Mulyo Agung (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2015)
This article aims to determine the internal Control section of the monitoring Fraud. Internal Control is the internal Control as a process that is influenced by the board of directors, management obtained from the information, and the employees are designed to provide assurance to ensure that the organization's objectives will be achieved. Information sub-system integrates both physical and non physical are interconnected and work together in harmony to achieve a goal of process data into information. In the complex internal control can be from the accounting information system, covering the scope of accounting transactions that cover all parts of the company, and the procedures in the process from the transaction until it generates financial reports. Accounting fraud in a behavior in which a person takes or intentionally dishonestly capitalize on others. Fraud or cheating which is a barrier to use resources efficiently, effectively and economically, so it is an important concern of management and the board of directors of the organization. From an accounting standpoint, cheating is a false depiction of the material facts in a ledger or financial statements.